Detection of the TYR Gene as a Candidate Causal Mutation for Albinism in Taro Cattle - Reza, Muhammad Aulia; Noor, Ronny Rachman; Jakaria, Jakaria; Margawati, Endang Tri (Jurnal Ilmu-Ilmu Peternakan, 2024)
Bali Cattle are known as cattle with a unique coat color pattern. At Taro village was found different coat colors of Bali cattle, namely Taro cattle perform white coat color. The TYR gene has a vital role in producing coat color. This research was aimed to determine mutations that caused of the white color in Taro cattle. Two methods of PCR and PCR-RFLP were applied in this study. PCR method followed by sequencing used 29 DNA samples consisted of 17 Taro cattle, 12 DNA samples of 3 breeds cattle as comparison while RFLP method applied 56 DNA samples (17 Taro; 31 wild Bali; 4 Simental, 4 PO/Ongole descendant). All DNA were collected from fresh blood, and extracted by using DNA Extraction Kit. Amplification of TYR (exon 5) gene was conducted using forward and reverse primers to get polymerase chain reaction products with lengths of 320 bp and sequenced with Sanger method (services). PCR-RFLP was conducted with enzyme restriction of AciI. Determination of TYR gene diversity was analyzed through sequencing data. TYR gene sequencing was analyzed by using Bioedit and Mega11 software to identify single nucleotide polymorphisms (SNPs). SNP genotyping was analyzed from PCR-RFLP. The results showed that the TYR gene (exon 5) of Taro cattle was found with 320 bp length. SNP was obtained at one position c.1467 T>C. This SNP has never been reported yet on the ensemble website. This finding suggests that a specific genetic marker for albinism in Bali cattle needs to be more explored